Beneficial and detrimental effects of genetic explanations for addiction. (December 2017) - Lebowitz, Matthew S; Appelbaum, Paul S
Background: Addictions are highly stigmatized and increasingly construed as biomedical diseases caused by genes, partly to reduce stigma by deflecting blame. However, genetic explanations may have negative effects, which have been understudied in the context of addiction. How the effects of genetic explanations might differ for substance addictions versus behavioral addictions is also unknown. Aims: This study examined the impact of genetic explanations for addiction on measures of treatment expectancies, blame, and perceived agency and self-control, as well as whether these varied depending on whether the addiction was to a substance or a behavior. Methods: Participants read about a person ('Charlie') with either alcohol use disorder or gambling disorder, receiving either a genetic or nongenetic explanation of Charlie's problem. They rated how much they blamed Charlie for his disorder, his likelihood of benefitting from medication or psychotherapy, and how much agency and self-control they ascribed to him. Results: Compared to the nongenetic explanation, the genetic explanation reduced blame and increased confidence in the effectiveness of pharmacotherapy. However, it also decreased the expected effectiveness of psychotherapy and reduced ascriptions of agency and self-control. Conclusion: Genetic explanations for addiction appear to be a 'double-edged sword', with beneficial effects that come at a cost.